In vitro determination of genotoxicity and cytotoxicity induced by stainless steel brackets with and without surface coating in cultures of oral mucosal cells - Dhruv Ahuja; Nidhin Philip Jose; Rozy Kamal; Vinaya Panduranga; Supriya Nambiar; Arun M. Isloor (BMC, 2024)
Abstract Background Orthodontics is a speciality of dentistry that uses a plethora of devices made from myriad materials to manage various malocclusions. Prolonged contact of orthodontic appliances with oral tissues can lead to cellular damage, highlighting the need for biocompatible materials to mitigate health risks. Objectives To analyze the genotoxicity and cytotoxicity produced by metal brackets and coated metallic brackets with polymeric and nanoparticle coatings in oral mucosal cells. Materials & methods The current study compares the toxicity of 3 different types of orthodontic brackets with control groups of oral mucosal cells. Each of the three treatment groups consisted of 10 samples of orthodontic brackets: stainless steel brackets(Group 1), nanoparticle-coated brackets(Group 2), and polymeric-coated brackets(Group 3) exposed to corrosion eluates employing an oral biomimicry model. Two types of oral mucosal cells- Human Gingival Fibroblasts and Buccal Epithelial Cells were used to study the cytotoxic and/or genotoxic effects of the elutes. Intergroup comparisons were conducted using one-way analysis of variance, while scanning electron microscopy evaluated surface characteristic. Results The interaction between metal ions and oral mucosal cells showed no statistically significant difference for toxicity assays between the three groups(p > 0.005). However, polymeric and nanoparticle-coated groups showed reduced cellular differentiation when compared with conventional stainless-steel brackets. Conclusion This in-vitro study shows that polymeric or nanoparticle coating of conventional metal brackets aids in enhancing corrosion-resistant characteristics of orthodontic appliances and reduces the toxic oral environment created by metal release in the oral cavity.